Java programming for the absolute beginner - Flynt, John P. (Thomson Course Technology PTR, 2007)
Java Programming for the Absolute Beginner provides you with an introduction to Java that allows you to learn the fundamentals of object-oriented programming while becoming acquainted with many of the core features of Java. This book starts with the assumption that you have not previously written a computer program. It then walks you through the creation of a variety of games and applications. After you have your footing with the basics, you learn to develop your own systems of classes, and by the end of the book, you are working with many of Java's Graphical User Interface (GUI) features and developing a desktop Windows application. This book provides a solid introduction for anyone desiring a relaxed, fully guided tour of the fundamentals of Java, programming, and the object-oriented approach to application development.